2008
DOI: 10.1590/s0034-89102008000800006
|View full text |Cite
|
Sign up to set email alerts
|

Uso do preservativo: tendências entre 1998 e 2005 na população brasileira

Abstract: OBJECTIVE:To analyze the levels, tendencies and sociodemographic differentials of condom use among the Brazilian urban population. METHODS:The data analyzed was collected in 1998 and 2005, in the study, "Sexual Behavior and Perceptions of the Brazilian Population concerning HIV/ Aids". The probabilistic samples, in multiple stages, included men and women aged 16 to 65 years old, living in urban areas. Interviews with individuals that had been sexually active during the 12 months preceding the interview were in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
23
2
33

Year Published

2010
2010
2015
2015

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(67 citation statements)
references
References 4 publications
8
23
2
33
Order By: Relevance
“…13,14 . A evidência encontrada em um daqueles estudos 14 , comprovando que os homens jovens utilizam mais o preservativo masculino em comparação às mulheres, não foi observada nesta pesquisa.…”
Section: Discussionunclassified
See 1 more Smart Citation
“…13,14 . A evidência encontrada em um daqueles estudos 14 , comprovando que os homens jovens utilizam mais o preservativo masculino em comparação às mulheres, não foi observada nesta pesquisa.…”
Section: Discussionunclassified
“…13,14 . A evidência encontrada em um daqueles estudos 14 , comprovando que os homens jovens utilizam mais o preservativo masculino em comparação às mulheres, não foi observada nesta pesquisa. Por sua vez, a forte tendência de aumento do uso da pílula entre a primeira e a última relação sexual, principalmente entre as mulheres, e a diminuição da proporção de uso do preservativo masculino, embora tenha permanecido elevada, estão em acordo com os resultados obtidos em outros estudos 1,3,15 .…”
Section: Discussionunclassified
“…The reference to never using a condom, or only sometimes, is more prevalent in several studies conducted in other TCCs in the country (3,11,12) . The statement by Kaplan et al (13) that there was significant increase in the search for condoms after the 1980s is reaffirmed by Berquó et al (2) , who exposes there was an increase, from 63.5% to 78.6%, in the use of condoms among people with occasional partners from 1998 to 2005. A study conducted in Santa Catarina observed that the frequency of non-use of condoms with a non-fixed partner is higher than 50% for both sexes, which shows that such use is below expectations (12) .…”
Section: Discussionmentioning
confidence: 88%
“…Still, the use of condoms to prevent STIs is reduced, especially among specific groups of the population, such as younger women or those with stable partners and people with lower schooling (2) . The absence of condom use with non-fixed partners is related to the unequal gender relations, schooling, moral and religious factors, practice of commercial sex, sexual preference, existence of a single partner (2) , besides social condition and exclusion situations resulting from adolescence (3) , among others. An investigation conducted in Testing and Counseling Centers (TCC) with adults observed that, for both sexes, with no distinction as to marital status, 86.6% used condoms only sometimes in intercourse with non-fixed partners (4) .…”
Section: Introductionmentioning
confidence: 99%
“…A atuação dos profissionais na atenção à saúde sexual e reprodutiva ainda esbarra nesse problema e parece, ao menos nos serviços pesquisados, estar longe de alcançar um discurso e um trabalho integrados, na direção de repensar a reprodução como um processo relacional, que envolve diretamente a sexualidade e no qual a inserção dos homens seja redimensionada de um papel instrumental (como aquele que apóia ou dificulta as decisões de suas parceiras) para o lugar de sujeitos que se reproduzem e podem regular sua fecundidade (Figueroa-Perea, 1998 A pouca distribuição de camisinhas e a escassez de iniciativas que divulguem e promovam essa atividade se torna ainda mais problemática diante do cenário configurado pelo (não) uso da camisinha. A despeito de haver procura nos serviços e grande aceitação na distribuição feita fora deles, a introdução da camisinha nas práticas sexuais, mesmo que tenha aumentado nos últimos anos, sobretudo entre os jovens (Paiva et al, 2006;2008b;Berquó et al, 2008), ainda é insatisfatória se considerarmos o crescente número de infecções por DST/AIDS.…”
Section: Abordagem à Sexualidade Masculina Na Apsunclassified